Artificial Intelligence-Powered Development of Location Image Analysis Algorithm using Image Crawling and Deep Learning - Jang , Jin-Wook (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The research study was conducted for development of the advanced image analysis service system based on deep learning. CNN (Convolutional Neural Network) is built in this system to extract learning data collected from Google and Instagram. The service gets a place image of jeju island as an input and provides relevant location information of it based on its own learning data. The process in 6 primary parts starts by collecting image data, converting it into appropriate format, and perform training and prediction, filtering invalid training data and repeats the Learning Part. Accuracy improvement plans are applied throughout this study. In conclusion, the implemented system shows about 79.2% of prediction accuracy. When the system has plenty of learning data, it is expected to predict various places more accurately.